DEPARTMENT OF GEOGRAPHY SENIOR STUDENTS’ SELF-EFFICACY BELIEFS REGARDING GEOGRAPHY - Fatih AYDIN; Mustafa SAĞDIÇ (International Journal of Eurasia Social Sciences, 2016)
In this study, the self efficacy beliefs of final year students in the department of geography have been analyzed in terms of different variables. 90 senior class students studying at Karabuk University Faculty of Arts in Turkey, the department of geography in the 2014-2015 academic year participated in the study. The screening model was implemented. The self-efficacy belief scale related to geography” developed by Karadeniz (2005) was used as data collection tool. The scale consists of three subscales and totally 19 items. To analyze the data, in addition to the descriptive statistics, t- test and one-way analysis of variance were used. According to the obtained results, it was determined that Senior students of department of Geography self-efficacy scores level on Geography department was significantly different in the context of gender. There was no statistically significant difference according to learning level.